Management of cancer-associated disseminated intravascular coagulation. Issue 140 (April 2016) - Levi, Marcel
ABSTRACT: Cancer may be complicated by the occurrence of disseminated intravascular coagulation (DIC). DIC is characterized by a widespread and intravascular activation of coagulation (leading to intravascular fibrin deposition) and simultaneous consumption of coagulation factors and platelets (potentially resulting in bleeding). Clinically, DIC in cancer has in general a less fulminant presentation than the types of DIC complicating sepsis and trauma. A more gradual, but also more chronic, systemic activation of coagulation can proceed subclinically. Eventually this process may lead to exhaustion of platelets and coagulation factors and bleeding (for example at the site of the tumor) may be the first clinical symptom indicating the presence of DIC. In some cases, the clinical presentation of DIC in cancer may be reminiscent of thrombotic microangiopathies, which is understandable in view of the role of endothelium in both conditions. The therapeutic cornerstone of DIC is treatment of the underlying disorder but supportive treatment, specifically aimed at the hemostatic system may be required. Highlights: Activation of coagulation in cancer patients may lead to disseminated intravascular coagulation (DIC) DIC in cancer is driven by induction of cytokine and expression of procoagulant factors on cancer cells, such as tissue factor or factor X-activating cancer procoagulant Derangement of vascular endothelium plays a major role in the pathogenesis of cancer-induced DIC In the management of cancer-associated DIC anticoagulants are crucial, whereas antifibrinolytic agents may be helpful to manage excessive hyperfibrinolysis and bleeding